FEATURES OF THE SIXTH TECHNOLOGICAL PARADIGM (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The sixth technological paradigm marks a new phase in economic and societal development, driven by the integration of key technologies such as artificial intelligence, the Internet of Things, big data, biotechnology, 3D printing, and quantum computing. These innovations are transforming production processes, enhancing sustainability, and boosting global competitiveness. This paper explores the core features of the sixth paradigm, including its impact on labor markets, education, environmental sustainability, and international relations. Risks such as digital inequality and data security challenges are also addressed. Based on current forecasts, the article emphasizes the need for investment in human capital and digital infrastructure. The sixth paradigm is presented as a foundation for a more sustainable and equitable global future.
Keywords: sixth technological paradigm; artificial intelligence; Internet of Things; 3D printing; biotechnology; quantum technologies; digitalization; sustainable development; digital inequality; data security; innovation; technological leadership.